EFEKTIVITAS PENERAPAN PENDEKATAN SAINTIFIK MATA KULIAH BAHASA INDONESIA DI STAI AL FALAH BANJARBARU - Arafat, Yasir (STAI AL FALAH Banjarbaru, 2018)
The focus of this paper is on the effectiveness of applying the Indonesian language learning approach at STAI Al Falah Banjarbaru. The aim is to determine the effectiveness of the application of scientific approaches which include: observing, asking, trying, reasoning and communicating. The method used is descriptive qualitative, which functions to see, review, know and expose and express things according to what they are. Data collection techniques use observation, interview, and documentation techniques. While the data analysis technique was carried out in a qualitative descriptive manner. As for the findings and discussions gathered through observation, interviews, and documentation, about the effectiveness of the application of scientific approaches to Indonesian language courses in STAI Al Falah Banjarbaru, can be described as follows: (1) Application of scientific approaches to observing aspects, ask, try and communicate has been implemented optimally. (2) for the aspect of reasoning cannot be done well. Keywords: Effectiveness, scientific approach